2011
DOI: 10.1002/jsfa.4307
|View full text |Cite
|
Sign up to set email alerts
|

Effect of amino acid level in the pig diet during growing and early finishing on growth response during the late finishing phase of lean meat type gilts

Abstract: In the lean meat type gilts used in this experiment, restricting amino acid concentrations by 20% in the growing and 30% in the early finishing phase increased the growth rate and efficiency of growth in the subsequent late finishing phase. In order to obtain good carcass quality, it is crucial to provide the animals with a balanced diet during the late finishing phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 19 publications
2
11
2
Order By: Relevance
“…Similarly, the greater ADG for the MP group vs. LP during the finisher phase I was associated with a greater gain:feed ratio for the former. These results, which were similar to the increased lysine and feed efficiencies during the compensatory growth of growing-finishing pigs in previous studies [12, 29], suggest that the increased ADG in the aforementioned LP and MP groups resulted from a compensatory growth to make up for the reduced weight gain during the preceding phase. Moreover, the similar ADG for the LP-1 and LP-2 groups during the finisher phase II provided with the isocaloric diets containing 0.85% and 0.72% lysine, respectively, suggest that a 0.72% dietary lysine content, which is similar to the NRC [22] recommendation (0.71% for 100–135 kg pigs), is probably enough for the finishing pigs weighing approximately 95 kg or greater.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similarly, the greater ADG for the MP group vs. LP during the finisher phase I was associated with a greater gain:feed ratio for the former. These results, which were similar to the increased lysine and feed efficiencies during the compensatory growth of growing-finishing pigs in previous studies [12, 29], suggest that the increased ADG in the aforementioned LP and MP groups resulted from a compensatory growth to make up for the reduced weight gain during the preceding phase. Moreover, the similar ADG for the LP-1 and LP-2 groups during the finisher phase II provided with the isocaloric diets containing 0.85% and 0.72% lysine, respectively, suggest that a 0.72% dietary lysine content, which is similar to the NRC [22] recommendation (0.71% for 100–135 kg pigs), is probably enough for the finishing pigs weighing approximately 95 kg or greater.…”
Section: Discussionsupporting
confidence: 90%
“…In the studies of Castell et al [30] and Kerr et al [34], the backfat thickness of the pigs reared on the low-lysine diets during the entire grow-finish period was greater than that of the pigs fed the diets with optimal lysine:calorie ratios. The pigs fed the low-lysine diet had a lower ADG and a greater backfat thickness than those on the diet with a normal lysine concentration during the grower phase in the studies of Fabian et al [18, 19] and Millet et al [29, 35] as well. However, when both groups of pigs were placed on a diet with an optimal lysine:calorie ratio during the finisher phase, the former exhibited a backfat thickness equal to that of the latter at the end of the finisher phase as a result of a compensatory lean growth in these studies.…”
Section: Discussionmentioning
confidence: 95%
“…This could have been a consequence of both a lack of the limiting EAA and an imbalance in the EAA profile, which seems to be apparent when applying the Swiss recommendations (Agroscope, 2015). This assumption is confirmed by results of the study of Millet et al (2011), where growing and finishing pigs used the amino acids more efficiently when fed low amino acid diets. Despite the aforementioned presumed EAA imbalances, low CP pigs were 10% more efficient than control pigs in the finisher II period.…”
Section: Nitrogen Efficiencysupporting
confidence: 55%
“…Good amino acid balance is essential for animal feed efficiency. Millet et al (2011) found that restricting amino acid levels in pigs' diets during growing and early finishing led to decreased growth rates. According to Toride (2002), for growing pigs, the limiting amino acid sequence is lysine, threonine, and tryptophan, and for broilers, the sequence is methionine, lysine, and threonine.…”
Section: Discussionmentioning
confidence: 99%